The Influence of Cybercriminal Activities to the Human Society - Okechukwu Chimaogu Wori (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
Cybercrime has increased exponentially in conjunction with the introduction and widespread use of electronic medium. As the technological advancements take shape, so do the systems of evolution of cybercrime. This implies that new forms of cybercrime are emerging to counter the new technological innovations, which has led to an increased concern in the whole endeavor of crime on the internet. Most users of the online applications are weary about the increasing trend of criminal activities, where in real essence, if these harms are not regulated, the use of the internet would be akin to vulnerability to both social and economic risks. This is not just confined to one area, but rather is occurring worldwide. Some progress has been made to counter this type of crime, but criminal legislation which crosses international borders is severely lagging behind. It is imperative that with the increasing advancement in the levels of crime, all the stakeholders must come up with proactive measures that could help resolve this issue for once and for all for a moral definition of the sue of the internet. Some sort of public policy must be adopted, according to individuals, educational institutions, organizations and corporations who are interested in combating this wave of crime.